The Effect Of Heavy Rope Exercises On Developing Some Of The Physical Abilities Of A Freestyle Volleyball Player (Journal of the College of Basic Education, 2025)
The training process has taken an organizational form and structure that is consistent with the state of new development of methods and means used in the training process. Scientific and technical development has added many new and modern methods in a way that is compatible with the nature of the sports activity practiced and the age group of the trainees with the specialized sports activity in order to achieve the best results and invest privacy. Training related to the type of activity in order to have a direct effect on improving the skill, physical, functional, tactical, psychological and mental level of the player. It is also important to reach this highest sporting level It comes through the use of modern training methods, methods and means based on scientific foundations that are compatible with the rules and laws of sports training. Weight ropes are one of the modern training tools that aim to increase muscle strength through the stability provided by the ropes, which work to develop the freestyler’s performance level and then achieve the desired achievement. Thus, this study came to demonstrate the importance of using exercises with heavy ropes in developing some of the physical abilities of the freestyle volleyball player The research problem focused on the fact that diversity, change, and modernity are among the basic pillars for reaching the optimal training state, and this comes through continuous search for what is new and different and avoiding boredom within the training unit when performing physical exercises. Hence, the research problem emerged in using heavy rope exercises to develop some Physical abilities of a freestyle volleyball player he research aimed to prepare exercises with heavy ropes, and to identify the effect of exercises with heavy ropes to develop some of the physical abilities of the volleyball freestyle player. The research assumed that there are statistically significant differences between the pre- and post-tests among the research sample to develop some of the physical abilities of the volleyball freestyle player. The researcher used the experimental method with a design (one group with a pre-test and a post-test) to suit the nature of the research and its problem .As for the research community, the researcher identified the research community for the players of the Specialized School of Volleyball, which numbered (6) freestyle players. The exercises were carried out with heavy ropes on the day2024/6/2 for a day, and one of the most important conclusions of the research is that the curriculum with heavy ropes has a role in developing physical abilities and the accuracy of performing technical skills with the ball. The plane is in the experimental group. The research concluded the need to develop training curricula and use modern methods, tools and equipment, which are the basis for the success of the training unit and raising the level of players.